Antioxidant and Nutrient Profile of Tomato Processing Waste from the Mixture of Indigenous Croatian Varieties: Influence of Drying and Milling - Tea Petković; Emerik Galić; Kristina Radić; Nikolina Golub; Jasna Jablan; Maja Bival Štefan; Tihomir Moslavac; Karla Grudenić; Ivana Rumora Samarin; Tomislav Vinković; Dubravka Vitali Čepo (Applied Sciences)
Tomato processing waste (TPW) represents a valuable but underutilized by-product of the food industry with potential for valorization within bioeconomy models. This study investigated the chemical composition, antioxidant profile, and sanitary safety of TPW, analyzing the whole TPW; its fractions (peels and seeds) and oil are obtained from TPW seeds. All samples showed contaminant levels within regulatory limits, confirming their safety for further applications. Various drying methods (air-drying at 70 °C and at 50 °C, lyophilization and vacuum drying) and grinding intensities were evaluated to determine their impact on TPW bioactive compounds retention and organoleptic characteristics. TPW exhibited valuable nutritional properties, particularly high protein and dietary fiber content while TPW oil was characterized with high monounsaturated fatty acid content. Results demonstrated that drying method and particle size significantly influenced the yield of bioactive compound and organoleptic properties, with either lyophilization or vacuum drying and finer milling generally enhancing the recovery of polyphenols, β-carotene, and lycopene and improving color intensity. This research provides the first characterization of the TPW obtained from Croatian indigenous tomato varieties, establishing a scientific foundation for its sustainable valorization and, in broader terms, supporting circular economy objectives and contributing to more resource-efficient food systems.